Pavilion Serbia in Rome 1911. modernism, architecture and an early idea of Yugoslavia / Slobodan Danko Selinkić - Jankov, Sonja (Arhitektura i urbanizam, 2023)
Review of the interdisciplinary monograph Pavilion Serbia in Rome in 1911. Modernism, Architecture and the Early Idea of Yugoslavia by Slobodan Danko Selinkić, which is a valuable contribution to research about the sculptor Ivan Meštrović and the architect Petar Bajalović, as well as to history of cultural diplomacy, history of architecture and urbanism, typology of exhibition pavilions, cultural studies, cultural politics, studies of Yugoslavia and history.